2002
DOI: 10.7861/clinmedicine.2-1-45
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic targets in the rapidly expanding field of purinergic signalling

Abstract: -The concept of a purinergic signalling system, using purine nucleotides and nucleosides as extracellular messengers, was first proposed over 30 years ago. After a brief historical review and update of purinoceptor subtypes, this article focuses on the diverse physiological roles of adenosine triphosphate, adenosine diphosphate, uridine triphosphate and adenosine. These molecules mediate short-term (acute) signalling functions in neurotransmission, secretion and vasodilation, and long-term (chronic) signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 57 publications
1
78
0
1
Order By: Relevance
“…4a). This result was confirmed by quantitative analysis of the ecto-5′-NT/CD73 immunofluorescence, which increased in a time-response profile of BBN exposition (4,8,12,18, and 24 weeks). Moreover, it was observed that an increase in the areas of increased cell proliferation and decreased presence of umbrella cells are important pathological characteristics of a malignant bladder process.…”
Section: Pathological Analysissupporting
confidence: 55%
See 4 more Smart Citations
“…4a). This result was confirmed by quantitative analysis of the ecto-5′-NT/CD73 immunofluorescence, which increased in a time-response profile of BBN exposition (4,8,12,18, and 24 weeks). Moreover, it was observed that an increase in the areas of increased cell proliferation and decreased presence of umbrella cells are important pathological characteristics of a malignant bladder process.…”
Section: Pathological Analysissupporting
confidence: 55%
“…White scale bars= 25 μm. b Quantification of ecto-5′-NT/CD73 staining of bladder urothelium from mice which received BBN for 4,8,12,18, and 24 weeks. The immunofluorescent images of ecto-5′-NT/CD73 were quantified in MacBiophotonics ImageJ software as described in Materials and methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations